Theoretical and methodological assumptions of legacies preservation in libraries (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The aim of the paper is to develop a theoretical framework for the preservation of legacies with regard to the specifics that we find in libraries. The purpose of the paper is to create a theoretical and methodological starting point for further research that will make it possible to gain a more comprehensive insight into the state of preservation of legacies in libraries in the Republic of Croatia.Approach/methodology/design. A review of the relevant literature is presented, with a special focus on the consideration of terminological and legal issues and the issue of preservation, processing, organization and placement of legacies in libraries, as well as the issue of their evaluation and use.Findings. Based on theoretical considerations, insight was gained into the perception of legacies as values both for the library and for the wider local community. The notion of legacies in libraries is comprehensively defined from a whole range of points of view, and special emphasis is placed on possible obstacles and problems encountered by librarians in working with these special collections. The issue of legacies through various aspects of protection management was considered, which resulted in the definition of a comprehensive theoretical framework for the preservation of legacies in libraries.Research limitations/implications. The issue of legacies, their organization and preservation in the Republic of Croatia has not been systematically researched so far. Obstacles to working with legacies are most often visible through scattered data on collections and/or the lack of records of heritage collections at the national level. There is also a large number of unprocessed collections due to the lack of staff, financial and spatial constraints, which results in the unavailability of materials for users, and unrecognized legacies as values at the institutional, regional and national levels.Practical implications. This paper should be seen as a basic contribution to the systematic consideration of legacies in libraries, their organization, preservation and presentation in the context of cultural heritage as one of the main identity features.Originality/value. Different approaches to the processing, organization, storage and availability of legacies in libraries are possible. The paper presents the theoretical framework of this issue and presents general data on legacies, their management, organization and preservation. The elaboration of the theoretical framework for the preservation of legacies in libraries is the starting point for further comprehensive and systematic research of legacies as a very important part of the entire corpus of our cultural heritage. In doing so, special attention should be paid to the issue of implementation of effective solutions in library practice.
Keywords: legacy; legacy management; legacy preservation; special collections